Short-term determination and long-term evaluation of the dietary methionine requirement in adult dogs. Issue 12 (28th June 2020) - Harrison, Matthew; Thomas, Gaelle; Gilham, Matthew; Gray, Kerry; Colyer, Alison; Allaway, David
Abstract: Methionine, an essential sulphur-containing amino acid (SAA), plays an integral role in many metabolic processes. Evidence for the methionine requirements of adult dogs is limited, and we employed the indicator amino acid oxidation (IAAO) method to estimate dietary methionine requirements in Labrador retrievers ( n 21). Using semi-purified diets, the mean requirement was 0·55 (95 % CI 0·41, 0·71) g/4184 kJ. In a subsequent parallel design study, three groups of adult Labrador retrievers ( n 52) were fed semi-purified diets with 0·55 g/4184 kJ (test diet 1), 0·71 g/4184 kJ (test diet 2) or 1·37 g/4184 kJ (control diet) of methionine for 32 weeks to assess the long-term consequences of feeding. The total SAA content (2·68 g/4184 kJ) was maintained through dietary supplementation of cystine. Plasma methionine did not decrease in test group and increased significantly on test diet 1 in weeks 8 and 16 compared with control. Reducing dietary methionine did not have a significant effect on whole blood, plasma or urinary taurine or plasma N-terminal pro B-type natriuretic peptide. Significant effects in both test diets were observed for cholesterol, betaine and dimethylglycine. In conclusion, feeding methionine at the IAAO-estimated mean was sufficient to maintain plasma methionine over 32 weeks when total SAA was maintained. However, choline oxidation may have increased to support plasma methionine and have additional consequences for lipid metabolism. While the IAAO can be employed to assess essential amino acid requirements, such as methionine in the dog using semi-purified diets, further work is required to establish safe levels for commercial diet formats.